Frankenstein alive, alive! the complete collection - Niles, Steve 1965-; Wrightson, Bernie 1948-2017 (IDW Publishing, 2022)
"Inspired by Mary Shelley's immortal gothic horror tale, Frankenstein alive, alive! continues the story of Victor Frankenstein's Promethean monster as the creature embarks on a journey to discover his own humanity."--Cover
Keywords: Frankenstein -- Fiktive Gestalt; Wissenschaftler; Ungeheuer; Frankenstein's Monster / (Fictitious character) / Fiction; Frankenstein, Victor / (Fictitious character) / Comic books, strips, etc; Monsters / Comic books, strips, etc; Scientists / Comic books, strips, etc; Science fiction comic books, strips, etc; Monsters; Scientists; Gothic fiction; Fantasy comics; Comics (Graphic works); Science fiction comics; Horror comics; Comic